Erythema Sweetobullosum: A Reactive Cutaneous Manifestation of Coccidioidomycosis - Hisham Abukamleh MD; Arash Heidari MD; Greti Petersen MD; Piruthiviraj Natarajan MD; Gian Yakoub MD; Everardo Cobos MD; Royce Johnson MD (SAGE Publishing, 2018)
Reactive cutaneous coccidioidal skin manifestations are commonly noticed during the early stage of coccidioidomycosis. These skin lesions are devoid of any active coccidioidal organism, and the immune trigger mechanisms are not elucidated. We describe 6 cases of unusual reactive cutaneous coccidioidal manifestation, characterized by painful vesiculobullous lesions known as erythema sweetobullosum. The biopsy of the lesions revealed neutrophilic dermatosis with inflammatory cells resulting in a cleft and elevation of the most superficial layer of the skin forming a bulla. The reactive cutaneous lesion is self-limited and requires no specific therapy.